Quality of life of persons with profound intellectual and multiple disabilities: A narrative literature review of concepts, assessment methods and assessors. Issue 3 (3rd July 2019) - Nieuwenhuijse, Appolonia M.; Willems, Dick L.; van Goudoever, Johannes B.; Echteld, Michael A.; Olsman, Erik
ABSTRACT: Background: The objective of this study was to provide an overview of concepts, methods of assessment and assessors in empirical studies on quality of life (QoL) of persons with Profound Intellectual and Multiple Disabilities (PIMD). Method: A narrative literature review was conducted by searching electronic databases until December 2016, and the included studies were then analysed thematically. Results: Twenty-one articles were included in the analysis. Multidimensional concepts of QoL consisting of both subjective and objective components were found, although the articles used different distinctions for each. QoL was assessed by behavioural observations or interviews/questionnaires. Family members, primary caregivers and more distant observers (or a combination of these three) determined QoL. Triangulation of assessors and methodological pluralism were used. Conclusions: This review highlighted several components of QoL in persons with PIMD, as well as challenges in researching the QoL of persons who are not able to express themselves verbally. The distinction between objective and subjective QoL was difficult to clarify, with interpretation being both inevitable and necessary. Although triangulation is seen to be good practice in QoL assessment, the role of proxies in assessing the QoL of persons with PIMD needs further investigation.